The effect of pasteurization on trace elements in donor breast milk - Mohd Taufek, Nor Hidayah; Cartwright, David William; Davies, Mark W.; Hewavitharana, Amitha K; Koorts, Pieter J.; McConachy, Helen; Shaw, Paul Nicholas; Sumner, Ronald; Whitfield, Karen M. (Nature Publishing Group, 2016)
OBJECTIVE: Premature infants often receive pasteurized donor human milk when mothers are unable to provide their own milk. This study aims to establish the effect of the pasteurization process on a range of trace elements in donor milk. STUDY DESIGN: Breast milk was collected from 16 mothers donating to the milk bank at the Royal Brisbane and Women’s Hospital. Samples were divided into pre- and post-pasteurization aliquots and were Holder pasteurized. Inductively coupled plasma mass spectrometry was used to analyze the trace elements zinc (Zn), copper (Cu), selenium (Se), manganese (Mn), iodine (I), iron (Fe), molybdenum (Mo) and bromine (Br). Differences in trace elements pre- and post-pasteurization were analyzed. RESULTS: No significant differences were found between the trace elements tested pre- and post-pasteurization, except for Fe(P<0.05). The median (interquartile range, 25 to 75%; μg l− 1) of trace elements for pre- and post- pasteurization aliquots were—Zn: 1639 (888–4508), 1743 (878–4143), Cu: 360 (258–571), 367 (253–531), Se: 12.34 (11.73–17.60), 12.62 (11.94–16.64), Mn:(1.48 (1.01–1.75), 1.49 (1.11–1.75), I (153 (94–189), 158 (93–183), Fe (211 (171–277), 194 (153–253), Mo (1.46 (0.37–2.99), 1.42(0.29–3.73) and Br (1066 (834–1443), 989 (902–1396).CONCLUSIONS: Pasteurization had minimal effect on several trace elements in donor breast milk but high levels of inter-donor variability of trace elements were observed. The observed decrease in the iron content of pasteurized donor milk is, however, unlikely to be clinically relevant.